2012
DOI: 10.1002/jez.1725
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p38MAPKin the Induction ofHsp70 During Acute Thermal Stress in Red Blood Cells of the Gilthead Sea Bream,Sparus aurata

Abstract: The present study aimed to examine the expression and activation of MAPKs (p38 MAPK, ERK1/2, and JNKs) in red blood cells (RBCs) of the gilthead sea bream, Sparus aurata, during thermal stress and investigate their involvement in the expression of heat shock proteins. The data showed that only p38 MAPK is detected in RBCs of Sparus aurata and it is phosphorylated and activated during exposure to increased temperature. Induction of Hsp70 in thermally stressed RBCs was abolished in the presence of the p38 MAPK i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 73 publications
4
29
1
Order By: Relevance
“…Previous work has shown that all three studied kinases are expressed in the muscle and the heart (Feidantsis et al 2009(Feidantsis et al , 2012, but the liver is deficient of JNKs (Feidantsis et al 2012). Similarly, we detected only p38 MAPK and ERKs in the liver of fish in this study (Fig.…”
Section: Phosphorylation Of Mapkssupporting
confidence: 71%
“…Previous work has shown that all three studied kinases are expressed in the muscle and the heart (Feidantsis et al 2009(Feidantsis et al , 2012, but the liver is deficient of JNKs (Feidantsis et al 2012). Similarly, we detected only p38 MAPK and ERKs in the liver of fish in this study (Fig.…”
Section: Phosphorylation Of Mapkssupporting
confidence: 71%
“…; Feidantsis et al . ). Additionally, in the European sea bass, the levels of p38 MAPK and ERKs remained unchanged under the effect of different concentration of T supplementation.…”
Section: Discussionmentioning
confidence: 97%
“…) and fish ( Sparus aurata ) red blood cells under the effect of thermal stress (Feidantsis et al . ). Hsps are a wide family of conserved proteins, present in all organisms including fish (Basu et al .…”
Section: Introductionmentioning
confidence: 97%
“…oxidative stress, inflammation, temperature and osmotic changes [68], [69], [70], [71], [72]. Several genes related to the components of MAPK signalling cascade (MAPKs as well as genes regulated by MAPK) including ERK1-ERK2 cascade ( mknk2a , mknk2b , fos , junbl , rps6ka1 , egfra ) and MAPK signalling ( daxx ) were significantly induced during the transport process.…”
Section: Discussionmentioning
confidence: 99%